Effect of optimal antenatal care on maternal and perinatal health in Ethiopia - Tesfay, Neamin; Hailu, Girmay; Woldeyohannes, Fitsum (Frontiers in Pediatrics, 2023)
Abstract Introduction Receiving at least four antenatal care (ANC) visits have paramount importance on the health of mothers and perinates. In Ethiopia, several studies were conducted on ANC service utilization; however, limited studies quantified the effect of care on maternal and perinate health. In response to this gap, this study is conducted to quantify the effect of optimal ANC care(≥4 visits) on maternal and perinatal health among women who received optimal care in comparison to women who did not receive optimal care. Methods The study utilized the Ethiopian perinatal death surveillance and response (PDSR) system dataset. A total of 3814 reviewed perinatal deaths were included in the study. Considering the nature of the data, preferential within propensity score matching (PWPSW) was performed to determine the effect of optimal ANC care on maternal and perinatal health. The effect of optimal care was reported using average treatment effects of the treated [ATT]. Result The result revealed that optimal ANC care had a positive effect on reducing perinatal death, due to respiratory and cardiovascular disorders, [ATT=-0.015,95%CI(-0.029 to -0.001)] and extending intrauterine life by one week [ATT=1.277,95%CI0.563-1.991)]. While it’s effect on maternal health includes, avoiding the risk of having uterine rupture [ATT=-0.012,95%CI:(-0.018 to -0.005)], improving the utilization of operative vaginal delivery (OPD) [ATT=0.032,95%CI:(0.001-0.062)] and avoiding delay to decide to seek care [ATT=-0.187,95%CI:(-0.354 to -0.021)] Conclusion Obtaining optimal ANC care has a positive effect on both maternal and perinatal health. Therefore, policies and interventions geared towards improving the coverage and quality of ANC services should be the top priority to maximize the benefit of the care.